Resveratrol Relieves Gouty Arthritis by Promoting Mitophagy to Inhibit Activation of NLRP3 Inflammasomes - Fan W; Chen S; Wu X; Zhu J; Li J (Dove Medical Press, 2021)
Weimin Fan,1,2 Shixian Chen,1 Xianghui Wu,3 Junqing Zhu,1 Juan Li1,2 1Department of Rheumatic & TCM Medical Center, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 2School of Traditional Chinese Medicine, Southern Medical University, Guangzhou, People's Republic of China; 3Laboratory Animal Research Center, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of ChinaCorrespondence: Juan LiDepartment of Rheumatic & TCM Medical Center, Nanfang Hospital, Southern Medical University, No. 1838, Guangzhou North Road, Baiyun District, Guangzhou, People's Republic of ChinaTel + 0086-020-61641675Fax +86 20 61648308Email lijuan@smu.edu.cnBackground: Gouty arthritis (GA) is a common inflammatory disease with pain caused by the deposition of monosodium urate (MSU) crystals into joints and surrounding tissues. Resveratrol (Res), derived from grapes and peanuts and the traditional Chinese medicine (TCM) Reynoutria japonica for GA, acts against oxidation and inflammation. The present study aimed to investigate the therapeutic effect and mechanism of Res on GA.Methods: Arthritis rat models, MSU-induced peritonitis mouse models, and inflammatory models of mouse bone marrow-derived macrophage (BMDM) were used in this study. Enzyme-linked immunosorbent assay (ELISA), JC-1, histopathological, immunofluorescence, flow cytometry, Western blot methods were applied to observe the effects of resveratrol on NLRP3 inflammasomes and mitophagy.Results: Res significantly improves the gait score and synovitis of rats with GA and inhibits the peritoneal inflammation induced by MSU. Res inhibits the MSU-induced activation of NLRP3 inflammasomes by reducing the levels of IL-1β, IL-18, and Caspase-1 and the pyroptosis of macrophages. In addition, Res raises the level of mitochondrial membrane potential, inhibits the expression of P62 and Pink1, enhances the expressions of LC3B-II, Parkin, and TOMM20, and promotes mitophagy, while mitophagy inhibitors reverse the inhibitory effect of Res on the activation of NLRP3 inflammasomes.Conclusion: Res significantly improves GA, and the underlying mechanism might be inhibiting the activation of NLRP3 inflammasomes by triggering the Pink1/Parkin pathway to promote mitophagy.Keywords: gouty arthritis, inflammation, macrophages, Pink1/Parkin